In-situ synchrotron x-ray diffraction and thermal expansion of TiB2 up to ∼3050 °C. Issue 8 (July 2023) - Converse, Elizabeth Sobalvarro; Thorpe, Fox; Rivera, Jesus; Charalambous, Harry; King, Gabriella; Cahill, James T.; Du Frane, Wyatt L.; Kuntz, Joshua D.; McCormack, Scott J.
Abstract: There is an increasing interest in understanding the performance and properties of ultra-high temperature ceramics due to their high melting points (<3000 °C) that make them promising for extreme environment applications. In-situ high temperature X-ray diffraction experiments were performed on TiB2 beads up to ∼3050 °C. For these experiments, TiB2 powders were fabricated into spherical beads via gel casting methods and densified in a high temperature graphite furnace. These sample beads were then levitated in a conical nozzle levitator with reducing atmosphere (3% H2 -Ar) while being heated using a 400 W CO2 laser. During levitation a collimated synchrotron X-ray source was used to perform in-situ, temperature-dependent structural characterizations. The anisotropic coefficients of thermal expansion of TiB2 were characterized as a function of temperature up to ∼3050 °C. Elucidation of these properties are critical for the advancement of TiB2 ceramics and other transition metal di-borides for use in high temperature applications such as hypersonic platforms, nuclear reactors, and atmospheric re-entry.